Pengaruh Beban Kerja Dan Fasilitas Kerja Terhadap Kinerja Pegawai BPBD Kota Tasikmalaya - Dhea Ananda Kusnandar; Arga Sutrisna; Ai Kusmiati Asyiah (Lembaga Pengembangan Kinerja Dosen, 2024)
The formulation of the problem in this research is How do workload and work facilities influence the employees performance at Regional Disaster Management Agency (BPBD) of Tasikmalaya City. The purpose of this study is to determine the effect of workload and work facilities on employee performance. The method used in this study is quantitative with a census approach. The sampling technique used was saturated sampling with samples taken as many as 47 respondents. Data collection techniques used were observation, interviews, questionnaires and study literature. The analytical tool used in this research is multiple linear regression using the SPSS version 25. The result showed that Workload and Work Facilities simultaneously have a significant influence on Employee Performance. Workload partially has a significant influence on Employee Performance. Work facilities partially has a significant influence on Employee Performance.